2017
DOI: 10.1108/ijwhm-07-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

How managers of small-scale enterprises can create a health promoting corporate culture

Abstract: Purpose Small-scale enterprises (SSEs) are important for sustainable development in Europe and account for a significant proportion of private enterprises and their large contribution to employment. The purpose of this paper is to explore workplace health management (WHM) from the perspective of managers in SSEs in Norway and Sweden. Design/methodology/approach In-depth interviews with 18 managers in SSEs were conducted and a stepwise qualitative analysis was used. Findings The findings are presented as tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 40 publications
3
55
0
Order By: Relevance
“…Managers in this study reported a high workload, significant responsibility and long working hours, all of which align with previous research (Hagqvist et al, 2015). In previous studies, self-employed workers and managers referred to the concept of being 'always on' to describe their boundless work (Hilbrecht and Lero, 2014;Landstad et al, 2017). The feeling of being 'always on' was also apparent in our data.…”
Section: Category: Conflict As a Part Of The Dealsupporting
confidence: 89%
“…Managers in this study reported a high workload, significant responsibility and long working hours, all of which align with previous research (Hagqvist et al, 2015). In previous studies, self-employed workers and managers referred to the concept of being 'always on' to describe their boundless work (Hilbrecht and Lero, 2014;Landstad et al, 2017). The feeling of being 'always on' was also apparent in our data.…”
Section: Category: Conflict As a Part Of The Dealsupporting
confidence: 89%
“…The position of this study is to explore and contribute to knowledge about how mentioned external factors contribute to development of WHM in SSEs. Research about WHM and OHS in SSEs has more been focused on management culture (Meggeneder, 2007) and internal workplace-related strategies (Frick et al, 2000;Landstad et al, 2017).…”
Section: Previous Research: Whmmentioning
confidence: 99%
“…Studies have shown that most SSEs pay little attention to OHS issues (Andersson & Hägg, 2006;Breucker, 2001;Frick, Langaa Jensen, Quinlan, & Wilthagen, 2000: Hasle & Limborg, 2006 and that specific strategies are needed to implement solutions in SSEs European Agency for Safety and Health at Work, 2013b). Similarly, research also suggests that SSEs have limited competence in creating health-promoting workplaces (Landstad, Hedlund, & Vinberg, 2017;Moser & Karlqvist, 2004;Torp & Moen, 2006). Nevertheless, the European Network for Workplace Health Promotion (2001) states that SSEs have a unique ability to affect employee health positively because of factors such as the family atmosphere and SSE managers' immediate control of working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Self-employed individuals, when compared to regular employees, often report working longer and more irregular hours (Hagqvist, Toivanen and Vinberg 2016;Nordenmark et al 2012), often have higher work demands (Stephan and Roesler 2010), and many, especially men, experience being always on, constantly working (Landstad, Hedlund and Vinberg 2017;Hilbrecht and Lero 2014). Thus, it seems that self-employed individuals have high pressure at work and that work takes up a lot of their time, which are factors that increase levels of WIL and will be further investigated.…”
Section: Risk Factors For Development Of Liw and Wil In Self-employmentmentioning
confidence: 99%